2014
DOI: 10.1002/pros.22903
|View full text |Cite
|
Sign up to set email alerts
|

Biologic differences between peripheral and transition zone prostate cancer

Abstract: Background Prostate cancer arises in the transition zone (TZ) in approximately 20-25% of cases. Modern biopsy and surveillance protocols, and advances in prostate cancer imaging, have renewed interest in TZ prostate cancers. We compared TZ and PZ prostate cancer to determine if cancer location is independently associated with better outcomes. Methods We evaluated an expanded cohort of 1534 men who underwent radical prostatectomy between 1983 and 2003 with updated long-term clinical follow-up. Regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 27 publications
6
64
0
3
Order By: Relevance
“…This is consistent with data suggesting that tumors of the transition zone, which are 20-25% of all prostate tumors, show a specific morphological, 33 clinical, 34,35 biological, 36 and molecular [37][38][39] behavior. Furthermore, findings of the current study are similar to those of a recent study on tumor-negative prostate samplings, in which we found higher LINE-1 methylation levels in TURPs than in biopsies.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with data suggesting that tumors of the transition zone, which are 20-25% of all prostate tumors, show a specific morphological, 33 clinical, 34,35 biological, 36 and molecular [37][38][39] behavior. Furthermore, findings of the current study are similar to those of a recent study on tumor-negative prostate samplings, in which we found higher LINE-1 methylation levels in TURPs than in biopsies.…”
Section: Discussionsupporting
confidence: 92%
“…Luminal, basal, and neuroendocrine cells constitute the normal prostate epithelia in a roughly 60:40:1 ratio [ 2 ]. Prostate cancer (PCa) develops most often in the PZ, less often in the TZ, and rarely in the CZ [ 3 , 4 ]. Upon development of PCa, the ratio of luminal to basal percentages are greatly altered, with the luminal cells constituting >99% of the tumor [ 2 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prostate also has four anatomic zones: the transition zone (TZ), which contains 5% of the glandular tissue and accounts for around 25% of PCa; the central zone (CZ), which contains 20% of the glandular tissue and accounts for around 5% of PCa; the peripheral zone (PZ), which contains 70–80% of the glandular tissue and accounts for about 70% of PCa; and the non-glandular anterior fibromuscular stroma. Accurate localization of PCa within the TZ or the PZ is extremely important as TZ prostate cancer is associated with favorable pathologic features and better recurrence-free survival [2]. …”
Section: Introductionmentioning
confidence: 99%